La sensibilizzazione fonologica in lingua inglese LS - Gronchi, Michela (Educazione Linguistica Language Education, 2018)
The present paper discusses the results of an action-research study involving a 15-year-old student who was diagnosed with severe dyslexia after coming to Italy through international adoption. The study investigates the literature on language acquisition in cases of early deprivation and the implications of the phonological deficit in students with dyslexia in a foreign language learning environment. The essay also reports the results of a learning program concerning phonological awareness that has been delivered in a two-month period to the student. The program outlines a possible methodological and practical framework for raising phonemic awareness in secondary school students with dyslexia and offers suggestions for classroom practice.